The real exchange rate and the impact of its imbalance on economic performance in the Maghre countriesb An empirical study using dynamic autoregressive vector method for VARP Panel data - Belharch, aicha; barik, mourad (Journal of Research in Finance and Accounting, 2026)
The aim of the study was to determine the real exchange rate behavior in the Maghreb countries by the dynamic auto regressive vector method of panel datafor the périod (1990-2020),then calculate their misalignment and determine the effect of this misalignment on economic performance. The study found that the best predictor of forward real exchange rate behavior is the current real exchange rate , also the behavior of the Maghrebien real exchange rate does not follow a random walk , rather it revolves around a constant average and the time of its half-life adjustment is four and half years. The study also found a positive relationship between misalignment and both economic growth , net export and saving. while there was an inverse relationship between this misalignment and net foreign direct investesment.